Leiomyoma of the urinary bladder : a case report (2013)
ABSTRACT: The case of a 71-year-old woman who presented with one year history of pelvic pain and occasional dysuria is reported. Computed tomography and Magnetic Resonance Imaging revealed a well defined intramural bladder mass. The histological findings of the surgical specimen confirmed a leiomyoma of the urinary bladder. The clinical presentation, imaging findings and management of this relatively rare benign tumor are discussed.